Scaling functional traits to ecosystem processes: Towards a mechanistic understanding in peat mosses. (31st December 2018) - Mazziotta, Adriano; Granath, Gustaf; Rydin, Håkan; Bengtsson, Fia; Norberg, Jon
Abstract: The role of trait trade‐offs and environmental filtering in explaining the variability in functional traits and ecosystem processes has received considerable attention for vascular plants but less so for bryophytes. Thus, we do not know whether the same forces also shape the phenotypic variability of bryophytes. Here, we assess how environmental gradients and trade‐offs shape functional traits and subsequently ecosystem processes for peat mosses ( Sphagnum ), a globally important plant genus for carbon accumulation. We used piecewise Structural Equation Modeling (SEM) to understand how environmental gradients influence vital processes across levels of biological organization. We gathered data on functional traits for 15 globally important Sphagnum species covering a wide range of ecological preferences. Phenotypes lie along well‐established axes of the plant economic spectrum characterizing trade‐offs between vital physiological functions. Using SEM, we clarified the mechanisms of trait covariation and scaling to ecosystem processes. We tested whether peat mosses, like vascular plants, constrain trait variability between a fast turnover strategy based on resource acquisition via fast traits and processes, and a strategy of resource conservation, via slow traits and processes. We parameterized a process‐based model estimating ecosystem processes linking environmental drivers with architectural and functional traits. In our SEM approach the amount of variance explained varied substantially (0.29 ≤ R 2 ≤ 0.82) among traits and processes in Sphagnum, and the model could predict some of them with high to intermediate accuracy for an independent dataset. R 2 variability was mainly explained by traits and species identity, and poorly by environmental filtering. Some Sphagnum species avoid the stress caused by periodic desiccation in hollows via resource acquisition based on fast photosynthesis and growth, while other species are adapted to grow high above the water‐table on hummocks by slow physiological traits and processes to conserve resources. Synthesis. We contribute to a unified theory generating individual fitness, canopy dynamics and ecosystem processes from trait variation. As for vascular plants, the functional traits in the Sphagnum economic spectrum are linked into an integrated phenotypic network partly filtered by the environment and shaped by trade‐offs in resource acquisition and conservation. Abstract : Our results show that the functional traits in the Sphagnum economic spectrum are linked into an integrated phenotypic network partly filtered by the environment and shaped by trade‐offs in resource acquisition and conservation as for vascular plants. We contribute to a unified theory generating plant individual fitness, canopy dynamics, and ecosystem processes from trait variation.